Towards Open Access Self Archiving Policies: A Case Study of COAR - Roy, Bijan Kumar; Biswas, Subal Chandra; Mukhopadhyay, Parthasarathi (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2018)
This paper examines Open Access (OA) self archiving policies of different Open Access Repositories (OARs) affiliated to COAR (Confederation of Open Access Repositories) as partner institutes. The process of scrutiny includes three major activities – selection of databases to consult; comparison and evaluation of Open Access policies of repositories listed in the selected databases and attached to COAR group; and critical examination of available self archiving policies of these OA repositories against a set of selected criteria. The above steps lead to reporting the following results: key findings have been identified and highlighted; common practices have been analyzed in relation to the focus of this paper; and a best practice benchmark has been suggested for popularizing and strengthening OARs as national research systems. This paper may help administrators, funding agencies, policy makers and professional librarians in devising institute-specific self archiving policies for their own organizations.